Reactive organic-inorganic hybrid phosphorus-nitrogen flame retardant as well as preparation method and application thereof
By using reactive organic-inorganic hybrid phosphorus-nitrogen flame retardant in nylon materials, the reaction of nanoparticles with phosphorus compounds and polymers is formed to form an organic-inorganic hybrid composite with excellent flame retardant properties, and the nylon material is solved The problem of poor flame retardant performance has achieved efficient flame retardant modification.
Patent Information
- Application Number
- CN202411806082.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-01-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Unmodified nylon materials have poor flame retardant properties and are prone to fire. The existing flame retardant modification methods have problems of mechanical properties and poor compatibility.
Using reactive organic-inorganic hybrid phosphorus-nitrogen flame retardant, the inorganic nanoparticles are mixed with epoxy-containing coupling agent, and then reacted with phosphorus compounds to form reactive phosphorus-containing modified nanoparticles, and then with phenolic compounds. Polymerized with nitrogen-containing monomers to obtain a reactive phosphorus-nitrogen flame retardant, and finally compounded with polyamide to form an organic-inorganic hybrid composite material.
It significantly improves the flame retardant performance of nylon materials, can achieve the UL94 V0 level flame retardant effect at a lower addition amount, which is better than small molecule and inorganic powder flame retardants, and is simple in process and environmentally friendly.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of flame retardant materials, and in particular to a reactive organic-inorganic hybrid phosphorus-nitrogen flame retardant and a preparation method and application thereof. Background Art
[0002] Polyamide, commonly known as nylon (PA), is a general term for thermoplastics containing repeating amide groups in the main chain of a polymer molecule. Nylon is widely used in various fields because it has excellent mechanical properties, electrical properties, heat resistance, toughness, oil resistance, self-lubrication and other excellent properties. However, unmodified nylon has poor flame retardancy. The UL94 vertical combustion of common nylon can only reach V-2 level. At the same time, dripping will occur during the combustion process of nylon. It is a flammable material and is very easy to cause fire during use, seriously endangering people's safety. Therefore, flame retardant modification of nylon is very important.
[0003] There are currently two common methods for preparing flame-retardant nylon. The first method is to add flame retardants to nylon to achieve a flame retardant effect. The Chinese invention patent with application number CN202110699465.0 discloses that nylon resin, thermoplastic polyester, red phosphorus flame retardant, reinforcing material and compatibilizer are mixed and melt blended to prepare a red phosphorus flame retardant reinforced composite material. Although a certain flame retardant effect is achieved, red phosphorus is generally compatible with the nylon matrix, and a compatibilizer needs to be added. In order to achieve a flame retardant effect, a large amount of flame retardant is added, which will destroy the mechanical properties of the material, and reinforcing materials need to be added to compensate. Another method is a copolymerization flame retardant method, which introduces flame retardant units into polymer chains by chemical copolymerization. The Chinese patent with application number CN202110698571.7 uses a copolymerization method to introduce functionalized polysilsesquioxane into nylon to prepare nylon with flame retardant properties, giving the copolymerized nylon resin excellent weather resistance and flame retardant properties, and there is no problem of poor compatibility with the substrate. At present, since the method of copolymerization modification of flame retardancy is better than blending modification, it is of great significance to increase the types of copolymerization modified flame retardants and expand the application scope of copolymerization modification. Summary of the invention
[0004] The purpose of the present invention is to provide a reactive organic-inorganic hybrid phosphorus-nitrogen flame retardant and a preparation method and application thereof. The phosphorus-nitrogen flame retardant is used as a flame retardant for nylon and has excellent flame retardant properties.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: The present invention provides a method for preparing a reactive organic-inorganic hybrid phosphorus-nitrogen flame retardant, comprising the following steps: Mixing inorganic nanoparticles, an epoxy-containing coupling agent and an organic solvent to perform a first modification to obtain coupling agent-modified nanoparticles; The coupling agent-modified nanoparticles are mixed with a first phosphorus compound and subjected to a second modification to obtain reactive phosphorus-containing modified nanoparticles; A phenolic compound, formaldehyde, a nitrogen-containing monomer and an alkaline catalyst are mixed to carry out a polymerization reaction to obtain an intermediate product; The intermediate product is mixed with a second phosphorus compound to carry out a condensation reaction to obtain a reactive phosphorus-nitrogen flame retardant; the second phosphorus compound contains a bifunctional group or a multifunctional group; Compounding the reactive phosphorus-containing modified nanoparticles with a reactive phosphorus-nitrogen flame retardant to obtain a reactive organic-inorganic hybrid phosphorus-nitrogen flame retardant; The first phosphorus compound includes one or more of hydroxymethylphenylphosphinate, hydroxyethylidene diphosphonic acid, 2-carboxyethylphenylphosphinate, 3-hydroxyphenylphosphonic acid, (3-aminophenyl)phosphonic acid, (2-hydroxyphenyl)phosphonic acid, phosphasalicylic acid, phosphoric acid, phosphorous acid and polyphosphoric acid; The second phosphorus compound includes one or more of hydroxymethylphenylphosphinate, hydroxyethylidene diphosphonic acid, 2-carboxyethylphenylphosphinate, 3-hydroxyphenylphosphonic acid, (3-aminophenyl)phosphonic acid, (2-hydroxyphenyl)phosphonic acid, phosphasalicylic acid, phosphoric acid, phosphorous acid and polyphosphoric acid.
[0006] Preferably, the inorganic nanoparticles include silicon dioxide, titanium dioxide, copper oxide, zinc oxide, montmorillonite or aluminum oxide; The epoxy-containing coupling agent includes KH-560; The mass ratio of the epoxy-containing coupling agent to the inorganic nanoparticles is 1:5-20.
[0007] Preferably, the first phosphorus compound includes one or more of hydroxymethylphenyl hypophosphorous acid, hydroxyethylene diphosphonic acid, 2-carboxyethylphenyl hypophosphorous acid, 3-hydroxyphenylphosphonic acid, (3-aminophenyl)phosphonic acid, (2-hydroxyphenyl)phosphoric acid, phosphasalicylic acid, phosphoric acid, phosphorous acid and polyphosphoric acid; the molar ratio of the epoxy-containing coupling agent to the first phosphorus compound is 1:0.3~1.
[0008] Preferably, the temperature of the first modification is room temperature, and the time is 3-6 hours; the temperature of the second modification is 60-90° C., and the time is 1-3 hours.
[0009] Preferably, the phenolic compound includes one or more of phenol, o-cresol, p-cresol, bisphenol A, hydroquinone, resorcinol, catechol and cardanol; the nitrogen-containing monomer includes melamine or urea; the molar ratio of the phenolic compound to the nitrogen-containing monomer is 10:1~5; the molar ratio of the phenolic compound to formaldehyde is 1:0.6~2.
[0010] Preferably, the alkaline catalyst includes aqueous ammonia, sodium hydroxide or potassium hydroxide; the polymerization reaction temperature is 70-100° C., the reaction time is 2-4 hours, and the pH value is 8.5.
[0011] Preferably, the second phosphorus compound includes one or more of hydroxymethylphenyl hypophosphorous acid, hydroxyethylidene diphosphonic acid, 2-carboxyethylphenyl hypophosphorous acid, 3-hydroxyphenylphosphonic acid, (3-aminophenyl)phosphonic acid, (2-hydroxyphenyl)phosphoric acid, phosphasalicylic acid, phosphoric acid, phosphorous acid and polyphosphoric acid; the molar ratio of the phenolic compound to the second phosphorus compound is 10:1-5; The condensation reaction temperature is 80-100° C. and the reaction time is 1-4 hours.
[0012] Preferably, the mass ratio of the reactive phosphorus-containing modified nanoparticles to the reactive phosphorus-nitrogen flame retardant is 1:1-5.
[0013] The present invention provides a reactive organic-inorganic hybrid phosphorus-nitrogen flame retardant prepared by the preparation method described in the above technical solution, wherein the reactive groups contained include hydroxyl groups or carboxyl groups.
[0014] The present invention provides an application of the reactive organic-inorganic hybrid phosphorus-nitrogen flame retardant described in the above technical solution in polyamide, and the application method comprises: mixing and granulating the reactive organic-inorganic hybrid phosphorus-nitrogen flame retardant with polyamide to obtain a composite; the mass of the reactive organic-inorganic hybrid phosphorus-nitrogen flame retardant is 1 to 40% of the mass of the polyamide.
[0015] The invention provides a preparation method of a reactive organic-inorganic hybrid phosphorus-nitrogen flame retardant. The invention adopts an epoxy-containing coupling agent to modify inorganic nanoparticles to obtain inorganic nanoparticles containing epoxy groups (epoxy groups react with hydroxyl groups or carboxyl groups on phosphorus-containing compounds, and the remaining hydroxyl groups or carboxyl groups can react with polyamide to be linked to a molecular chain); phosphorus-containing compounds open epoxy groups on the surfaces of inorganic nanoparticles to obtain reactive phosphorus-modified inorganic nanoparticles; and simultaneously, phosphorus-containing compounds containing functional groups react with nitrogen-containing resins to obtain reactive phosphorus-nitrogen flame retardants (for example, hydroxyl groups on phosphorus-containing compounds react with hydroxyl groups in melamine formaldehyde resins, and the remaining carboxyl groups or hydroxyl groups react with polyamide to be linked to a molecular chain). The reactive phosphorus-containing modified inorganic nanoparticles and the reactive phosphorus-nitrogen flame retardant prepared by the present invention can react with nylon. The reactive phosphorus-containing modified inorganic nanoparticles and the reactive phosphorus-nitrogen flame retardant are compounded, and the reactive functional groups contained in the obtained reactive organic-inorganic hybrid phosphorus-nitrogen flame retardant can become components of polymer molecular chains by reacting with polyamide to form an organic-inorganic hybrid composite material, which is not easy to migrate, thereby improving the flame retardancy of nylon materials, being superior to existing small molecule flame retardants and inorganic powder flame retardants, and therefore having broad application prospects.
[0016] The preparation method of the present invention has a wide range of production raw materials, a simple synthesis process, is environmentally friendly, and has excellent flame retardant properties, and can be used to improve the flame retardant properties of nylon.
[0017] The reactive organic-inorganic hybrid phosphorus-nitrogen flame retardant prepared by the invention is used in polyamide, and when the addition amount thereof in nylon is 1-40wt%, a 94-V0 grade flame retardant effect can be achieved. DETAILED DESCRIPTION
[0018] In the present invention, unless otherwise specified, the raw materials or reagents used are commercially available products well known in the art.
[0019] The present invention provides a method for preparing a reactive organic-inorganic hybrid phosphorus-nitrogen flame retardant, comprising the following steps: Mixing inorganic nanoparticles, an epoxy-containing coupling agent and an organic solvent to perform a first modification to obtain coupling agent-modified nanoparticles; The coupling agent-modified nanoparticles are mixed with a first phosphorus compound and subjected to a second modification to obtain reactive phosphorus-containing modified nanoparticles; A phenolic compound, formaldehyde, a nitrogen-containing monomer and an alkaline catalyst are mixed to carry out a polymerization reaction to obtain an intermediate product; The intermediate product is mixed with a second phosphorus compound to carry out a condensation reaction to obtain a reactive phosphorus-nitrogen flame retardant; the second phosphorus compound contains a bifunctional group or a multifunctional group; Compounding the reactive phosphorus-containing modified nanoparticles with a reactive phosphorus-nitrogen flame retardant to obtain a reactive organic-inorganic hybrid phosphorus-nitrogen flame retardant; The first phosphorus compound includes one or more of hydroxymethylphenylphosphinate, hydroxyethylidene diphosphonic acid, 2-carboxyethylphenylphosphinate, 3-hydroxyphenylphosphonic acid, (3-aminophenyl)phosphonic acid, (2-hydroxyphenyl)phosphonic acid, phosphasalicylic acid, phosphoric acid, phosphorous acid and polyphosphoric acid; The second phosphorus compound includes one or more of hydroxymethylphenylphosphinate, hydroxyethylidene diphosphonic acid, 2-carboxyethylphenylphosphinate, 3-hydroxyphenylphosphonic acid, (3-aminophenyl)phosphonic acid, (2-hydroxyphenyl)phosphonic acid, phosphasalicylic acid, phosphoric acid, phosphorous acid and polyphosphoric acid.
[0020] The present invention mixes inorganic nanoparticles, an epoxy-containing coupling agent and an organic solvent, and performs a first modification to obtain coupling agent-modified nanoparticles; The coupling agent modified nanoparticles are mixed with the first phosphorus compound and subjected to a second modification to obtain reactive phosphorus-containing modified nanoparticles.
[0021] In the present invention, the inorganic nanoparticles preferably include silicon dioxide, titanium dioxide, copper oxide, zinc oxide, montmorillonite or aluminum oxide. The present invention has no special requirements on the particle size of the inorganic nanoparticles, and commercially available products known in the art can be used.
[0022] In the present invention, the epoxy-containing coupling agent preferably includes KH-560; the mass ratio of the epoxy-containing coupling agent to the inorganic nanoparticles is preferably 1:5-20, more preferably 1:6.6-10, and further preferably 1:8.
[0023] In the present invention, the first phosphorus compound includes one or more of hydroxymethylphenyl hypophosphorous acid, hydroxyethylene diphosphonic acid, 2-carboxyethylphenyl hypophosphorous acid, 3-hydroxyphenylphosphonic acid, (3-aminophenyl)phosphonic acid, (2-hydroxyphenyl)phosphoric acid, phosphasalicylic acid, phosphoric acid, phosphorous acid and polyphosphoric acid; when the first phosphorus compound is more than two of the above, the present invention has no special limitation on the ratio of different types of first phosphorus compounds, and any ratio is acceptable.
[0024] In the present invention, the molar ratio of the epoxy-containing coupling agent to the first phosphorus compound is preferably 1:0.3-1, more preferably 1:0.33-0.55, and further preferably 1:0.37-0.52.
[0025] In the present invention, the organic solvent is preferably ethanol; the present invention preferably uses an organic solvent to prepare an epoxy-containing coupling agent into a solution with a mass concentration of 1-5% (more preferably 3%), then adds inorganic nanoparticles, stirs for a first modification, then heats to a second modification temperature, adds a first phosphorus compound to the product, and performs a second modification.
[0026] In the present invention, the temperature of the first modification is preferably room temperature, the time is preferably 3-6 hours, more preferably 4-5 hours; the temperature of the second modification is preferably 60-90°C, more preferably 70°C, the time is preferably 1-3 hours, more preferably 2 hours. During the second modification, the epoxy groups in the coupling agent-modified nanoparticles react with the hydroxyl or carboxyl groups on the phosphorus-containing compound.
[0027] After the modification is completed, the present invention preferably filters the obtained product and then vacuum dries it to obtain reactive phosphorus-containing modified nanoparticles.
[0028] The present invention mixes phenolic compounds, formaldehyde, nitrogen-containing monomers and alkaline catalysts to carry out polymerization reaction to obtain an intermediate product; and mixes the intermediate product with a second phosphorus compound to carry out condensation reaction to obtain a reactive phosphorus-nitrogen flame retardant.
[0029] In the present invention, the phenolic compound preferably includes one or more of phenol, o-cresol, p-cresol, bisphenol A, hydroquinone, resorcinol, catechol and cardanol; when the phenolic compound is two or more of the above, the present invention has no special limitation on the ratio of different types of phenolic compounds, and any ratio is acceptable.
[0030] In the present invention, the nitrogen-containing monomer preferably includes melamine or urea; the molar ratio of the phenolic compound to the nitrogen-containing monomer is preferably 10:1-5, more preferably 10:2-5; the molar ratio of the phenolic compound to formaldehyde is preferably 1:0.6-2, more preferably 1:0.8-1.8, more preferably 1:1.5-1.6.
[0031] In the present invention, the alkaline catalyst preferably includes aqueous ammonia, sodium hydroxide or potassium hydroxide; the mass concentration of the aqueous ammonia is preferably 5-15%, more preferably 10%; the amount of the alkaline catalyst used can reach the required pH value of the reaction.
[0032] In the present invention, preferably, after mixing the phenolic compound and formaldehyde, a nitrogen-containing monomer is added, an alkaline catalyst is added to adjust the pH value, and the temperature is raised to the reaction temperature to carry out the polymerization reaction.
[0033] In the present invention, the polymerization reaction temperature is preferably 70-100° C., more preferably 75-80° C., the time is preferably 2-4 h, more preferably 3 h, and the pH value is preferably 8.5.
[0034] After the polymerization reaction is completed, the present invention does not need to perform any treatment. After the temperature is raised to the condensation reaction temperature, the second phosphorus compound is added to the obtained intermediate product for condensation reaction. During the polymerization reaction, the phenolic compound, formaldehyde and the nitrogen-containing monomer form a resin, and the hydroxyl group on the second phosphorus compound condenses with the hydroxyl group in the resin to form a flame retardant.
[0035] In the present invention, the second phosphorus compound includes one or more of hydroxymethylphenyl hypophosphorous acid, hydroxyethylene diphosphonic acid, 2-carboxyethylphenyl hypophosphorous acid, 3-hydroxyphenylphosphonic acid, (3-aminophenyl)phosphonic acid, (2-hydroxyphenyl)phosphoric acid, phosphasalicylic acid, phosphoric acid, phosphorous acid and polyphosphoric acid; when the second phosphorus compound is more than two of the above, the present invention has no special limitation on the ratio of different types of second phosphorus compounds, and any ratio is acceptable.
[0036] In the present invention, the molar ratio of the phenolic compound to the second phosphorus compound is preferably 10:1-5, more preferably 1:1.5-2.16, and further preferably 1:1.6-1.9.
[0037] In the present invention, the temperature of the condensation reaction is preferably 80-100° C., more preferably 80-90° C., and the time is preferably 1-4 h, more preferably 2-3 h.
[0038] After the condensation reaction is completed, the present invention preferably raises the temperature to 180° C. and keeps the temperature for 30 minutes to remove water, phenol and oligomer small molecules, discharges the material and cools it to room temperature to obtain a reactive phosphorus nitrogen flame retardant.
[0039] The present invention compounds the reactive phosphorus-containing modified nanoparticles with a reactive phosphorus-nitrogen flame retardant to obtain a reactive organic-inorganic hybrid phosphorus-nitrogen flame retardant.
[0040] The present invention has no particular limitation on the composite method. The reactive phosphorus-containing modified nanoparticles and the reactive phosphorus-nitrogen flame retardant may be ground and then mixed according to a process well known in the art.
[0041] In the present invention, the mass ratio of the reactive phosphorus-containing modified nanoparticles to the reactive phosphorus-nitrogen flame retardant is preferably 1:1-5, more preferably 1:3-4.
[0042] The present invention provides a reactive organic-inorganic hybrid phosphorus-nitrogen flame retardant prepared by the preparation method described in the above technical solution, wherein the reactive groups contained include hydroxyl groups or carboxyl groups.
[0043] In the reactive organic-inorganic hybrid phosphorus-nitrogen flame retardant of the present invention, the reactive group can react with polyamide.
[0044] The present invention provides an application of the reactive organic-inorganic hybrid phosphorus-nitrogen flame retardant described in the above technical solution in polyamide, and the application method comprises: mixing and granulating the reactive organic-inorganic hybrid phosphorus-nitrogen flame retardant with polyamide to obtain a composite; the mass of the reactive organic-inorganic hybrid phosphorus-nitrogen flame retardant is 1-40% of the mass of the polyamide, and more preferably 6-10%.
[0045] In the present invention, the reactive organic-inorganic hybrid phosphorus-nitrogen flame retardant is preferably ground into powder, mixed with polyamide for 4-6 minutes, and the obtained mixture is mixed and granulated by a twin-screw extruder and then dried to obtain a composite.
[0046] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0047] In the following examples, the filtration device used for filtration includes a Buchner funnel (caliber 95 mm), a suction filter bottle (500 mL) and a vacuum pump (2XZ-1 type rotary vane vacuum pump), and the pore size of the filter paper is 0.22~8μm.
[0048] Nano-silicon dioxide was TSP-H10 from Jiangsu Tianxing New Materials Co., Ltd., with a particle size of 20 nm and a specific surface area of 200 m 2 / g, bulk density 0.1g / cm 3 .
[0049] Example 1 Prepare 1000g of KH560 ethanol solution with a mass concentration of 1%, add 100g of nano-silica, and stir to react for 6h; increase the temperature to 90°C, drop 2.5g of phosphoric acid (concentration 85%), the molar ratio of KH560 (0.042mol) to phosphoric acid (0.022mol) is 1:0.52, react for 1h, filter, and vacuum dry in an oven. The vacuum degree of vacuum drying is 0.005MPa, the drying temperature is 150°C, and the drying time is 12h to obtain reactive phosphorus-modified nano-silica; 940 g (10 mol) of phenol, 500 g (6.16 mol) of formaldehyde (mass concentration 37%), 272 g (2.16 mol) of melamine and 31.2 g (mass concentration 10%) of ammonia water were added into a three-necked flask, the pH value was adjusted to 8.5, and the mixture was reacted at 80°C for 2 h; 416 g (1.94 mol) of 2-carboxyethylphenylphosphite was added, the temperature was raised to 100°C, the mixture was reacted for 2 h, the temperature was raised to 180°C, the mixture was kept warm for 30 min, the mixture was discharged and cooled to room temperature, and a reactive phosphorus-nitrogen flame retardant was obtained; Take 100 g of reactive phosphorus-containing nano-silicon dioxide and 300 g of reactive phosphorus-nitrogen flame retardant, grind them in a mortar for 30 minutes so that they can pass through a 500-mesh sieve, and obtain an organic-inorganic hybrid phosphorus-nitrogen flame retardant.
[0050] Example 2 Prepare 1000g of ethanol solution of KH560 with a mass concentration of 3%, add 200g of nano-silica, and stir for 6h; increase the temperature to 60°C, drop 5.5g of phosphoric acid (concentration 85%), the molar ratio of KH560 (0.127mol) to phosphoric acid (0.048mol) is 1:0.37, react for 2h, filter, and vacuum dry in an oven, the vacuum degree of vacuum drying is 0.005MPa, the drying temperature is 150°C, and the drying time is 12h to obtain reactive phosphorus-modified nano-silica; 940 g (10 mol) of phenol, 560 g (mass concentration 37%, 6.89 mol) of formaldehyde, 310 g (2.46 mol) of melamine and 10 g of sodium hydroxide were added into a three-necked flask to adjust the pH value to 8.5, and reacted at 80°C for 2 h; 324 g (1.51 mol) of 2-carboxyethylphenylphosphite was added, the temperature was raised to 90°C, and after reacting for 3 h, the temperature was raised to 180°C, and the temperature was kept for 30 min, the material was discharged and cooled to room temperature; a reactive phosphorus-nitrogen flame retardant was obtained; Take 100 g of reactive phosphorus-containing nano-silicon dioxide and 400 g of reactive phosphorus-nitrogen flame retardant, grind them in a mortar for 30 minutes so that they can pass through a 500-mesh sieve, and obtain an organic-inorganic hybrid phosphorus-nitrogen flame retardant.
[0051] Example 3 Prepare 1000g of 3% KH560 ethanol solution, add 200g of nano copper oxide, and stir for 6h; increase the temperature to 60°C, drop 5.5g of phosphoric acid (concentration 85%), the molar ratio of KH560 to phosphoric acid is 1:0.37, react for 2h, filter, and vacuum dry in an oven, the vacuum degree of vacuum drying is 0.005MPa, the drying temperature is 150°C, and the drying time is 12h to obtain reactive phosphorus-modified nano copper oxide; 940g (10mol) of phenol, 972g (mass concentration of 37%, 11.97mol) of formaldehyde, 372g (2.95mol) of melamine and 31.2g (mass concentration of 10%) of ammonia water were added into a three-necked flask, the pH value was adjusted to 8.5, and the mixture was reacted at 70°C for 3h; 372g (2.16mol) of hydroxymethylphenylphosphite was added, the temperature was raised to 80°C, the mixture was reacted for 4h, the temperature was raised to 180°C, the temperature was kept for 30min, the mixture was discharged and cooled to room temperature; a reactive phosphorus-nitrogen flame retardant was obtained; Take 100 g of reactive phosphorus-modified nano copper oxide and 300 g of reactive phosphorus-nitrogen flame retardant, grind them in a mortar for 40 minutes so that they can pass through a 500-mesh sieve, and obtain an organic-inorganic hybrid phosphorus-nitrogen flame retardant.
[0052] Example 4 Prepare 1000g of 3% KH560 ethanol solution, add 200g of nano titanium dioxide, and stir for 4h; increase the temperature to 70°C, add 12g of hydroxymethylphenylphosphite, the molar ratio of KH560 (0.127mol) to hydroxymethylphenylphosphite (0.070mol) is 1:0.55, react for 2h, filter, and vacuum dry in an oven, the vacuum degree of vacuum drying is 0.005MPa, the drying temperature is 150°C, and the drying time is 12h, to obtain reactive phosphorus-modified nano titanium dioxide; 940 g (10 mol) of phenol, 500 g (mass concentration 37%, 6.16 mol) of formaldehyde, 272 g (2.16 mol) of melamine and 31.2 g of ammonia water were added into a three-necked flask, the pH value was adjusted to 8.5, and the mixture was reacted at 70°C for 2 h; 416 g (1.94 mol) of 2-carboxyethylphenylphosphite was added, the temperature was raised to 100°C, the mixture was reacted for 2 h, the temperature was raised to 180°C, the mixture was kept at this temperature for 30 min, the mixture was discharged and cooled to room temperature; a reactive phosphorus-nitrogen flame retardant was obtained; Take 100 g of reactive phosphorus-containing nano-titanium dioxide and 400 g of reactive phosphorus-nitrogen flame retardant, grind them in a mortar for 30 minutes so that they can pass through a 500-mesh sieve, and obtain an organic-inorganic hybrid phosphorus-nitrogen flame retardant.
[0053] Example 5 Prepare 1000g of ethanol solution of KH560 with a mass concentration of 2%, add 200g of nano zinc oxide, and stir for 4h; increase the temperature to 60°C, add 8g of hydroxymethylphenyl hypophosphorous acid, the molar ratio of KH560 (0.085mol) to hydroxymethylphenyl hypophosphorous acid (0.046mol) is 1:0.54, react for 2h, filter, and vacuum dry in an oven. The vacuum degree of vacuum drying is 0.005MPa, the drying temperature is 150°C, and the drying time is 12h to obtain reactive phosphorus-modified nano zinc oxide; 940 g (10 mol) of phenol, 972 g (mass concentration 37%, 11.97 mol) of formaldehyde, 372 g (2.95 mol) of melamine and 31.2 g of ammonia water were added into a three-necked flask, the pH value was adjusted to 8.5, and the reaction was carried out at 70°C for 3 hours; 372 g (2.16 mol) of hydroxymethylphenyl hypophosphorous acid was added, the temperature was raised to 80°C, the reaction was carried out for 4 hours, the temperature was raised to 180°C, the temperature was kept for 30 minutes, the material was discharged and cooled to room temperature; a reactive phosphorus-nitrogen flame retardant was obtained; Take 100 g of reactive phosphorus-containing nano zinc oxide and 300 g of reactive phosphorus-nitrogen flame retardant, grind them in a mortar for 30 minutes so that they can pass through a 500-mesh sieve, and obtain an organic-inorganic hybrid phosphorus-nitrogen flame retardant.
[0054] Example 6 Prepare 1000g of 5% KH560 ethanol solution, add 400g of nano-silica, and stir for 6h; increase the temperature to 90°C, add 12g of hydroxymethylphenyl hypophosphorous acid, the molar ratio of KH560 (0.21mol) to hydroxymethylphenyl hypophosphorous acid (0.07mol) is 1:0.33, react for 1h, filter, and vacuum dry in an oven, the vacuum degree of vacuum drying is 0.005MPa, the drying temperature is 150°C, and the drying time is 12h, to obtain reactive phosphorus-modified nano-silica; 940 g (10 mol) of phenol, 500 g (mass concentration of 37%, 5.91 mol) of formaldehyde, 272 g (2.16 mol) of melamine and 31.2 g of ammonia water were added into a three-necked flask, the pH value was adjusted to 8.5, and the mixture was reacted at 70°C for 3 h; 416 g (1.94 mol) of 2-carboxyethylphenylphosphorous acid was added, the temperature was raised to 100°C, the mixture was reacted for 2 h, the temperature was raised to 180°C, the temperature was kept for 30 min, the mixture was discharged and cooled to room temperature; a reactive phosphorus-nitrogen flame retardant was obtained; 100 g of reactive phosphorus-containing nano-silica and 300 g of reactive phosphorus-nitrogen flame retardant were taken, and they were ground in a mortar for 30 min so that the mixture could pass through a 500-mesh sieve to obtain an organic-inorganic hybrid phosphorus-nitrogen flame retardant.
[0055] Application Example 1 Take 2000 g of nylon 66 (INVISTA Nylon Chemical (China) Co., Ltd., PA66 U3600 NC01) and 200 g of the organic-inorganic hybrid phosphorus nitrogen flame retardant prepared in Example 1, and mix them. The resulting mixture is extruded and granulated through a twin-screw extruder. The conditions are: temperature control of zone 1 at 256°C, temperature control of zone 2 at 260°C, temperature control of zone 3 at 265°C, temperature control of zone 4 at 270°C, temperature control of zone 5 at 270°C, temperature control of zone 6 at 270°C, head temperature at 265°C, melt temperature at 233°C, main engine current at 13A, main engine speed at 60RPM, and feed speed at 15rpm to obtain modified nylon 66.
[0056] Using the UL94-2018 test standard, the modified nylon 66 obtained achieved V0 flame retardancy, and its limiting oxygen index (LOI) was >27%.
[0057] Application Example 2 Take 2000 g of nylon 66 (INVISTA Nylon Chemical (China) Co., Ltd., PA66 U3600 NC01) and 150 g of the organic-inorganic hybrid phosphorus-nitrogen flame retardant prepared in Example 2, and mix the resulting mixture through a twin-screw extruder for granulation. The conditions are as follows: temperature control of zone 1 at 256°C, temperature control of zone 2 at 260°C, temperature control of zone 3 at 265°C, temperature control of zone 4 at 270°C, temperature control of zone 5 at 270°C, temperature control of zone 6 at 270°C, head temperature at 265°C, melt temperature at 233°C, main engine current at 13A, main engine speed at 60RPM, and feed speed at 15rpm to obtain modified nylon 66.
[0058] Using the UL94-2018 test standard, the modified nylon 66 achieved V0 flame retardancy, and its limiting oxygen index (LOI) was >27%.
[0059] Application Example 3 Take 2000 g of nylon 66 (INVISTA Nylon Chemical (China) Co., Ltd., PA66 U3600 NC01) and 120 g of the organic-inorganic hybrid phosphorus-nitrogen flame retardant prepared in Example 3, and mix them. The resulting mixture is extruded and granulated through a twin-screw extruder. The conditions are: temperature control of zone 1 at 256°C, temperature control of zone 2 at 260-265°C, temperature control of zone 3 at 265-270°C, temperature control of zone 4 at 270°C, temperature control of zone 5 at 270°C, temperature control of zone 6 at 265-270°C, head temperature at 260-268°C, melt temperature at 233°C, main engine current at 13A, main engine speed at 60RPM, and feeding speed at 10-15rpm to obtain modified nylon 66.
[0060] Using the UL94-2018 test standard, the modified nylon 66 achieved V0 flame retardancy, and its limiting oxygen index (LOI) was >27%.
[0061] Application Example 4 Take 2000 g of nylon 66 (INVISTA Nylon Chemical (China) Co., Ltd., PA66 U3600 NC01) and 150 g of the organic-inorganic hybrid phosphorus-nitrogen flame retardant prepared in Example 4 and mix them. The resulting mixture is extruded and granulated through a twin-screw extruder under the following conditions: temperature control of zone 1 at 256°C, temperature control of zone 2 at 260°C, temperature control of zone 3 at 265°C, temperature control of zone 4 at 270°C, temperature control of zone 5 at 270°C, temperature control of zone 6 at 270°C, head temperature at 265°C, melt temperature at 233°C, main engine current at 13A, main engine speed at 60RPM, and feed speed at 15rpm to obtain modified nylon 66.
[0062] Using the UL94-2018 test standard, the modified nylon 66 achieved V0 flame retardancy, and its limiting oxygen index (LOI) was >27%.
[0063] Application Example 5 Take 2000 g of nylon 66 (INVISTA Nylon Chemical (China) Co., Ltd., PA66 U3600 NC01) and 150 g of the organic-inorganic hybrid phosphorus-nitrogen flame retardant prepared in Example 5, and mix them. The resulting mixture is extruded and granulated through a twin-screw extruder. The conditions are: temperature control of zone 1 at 256°C, temperature control of zone 2 at 260°C, temperature control of zone 3 at 265°C, temperature control of zone 4 at 270°C, temperature control of zone 5 at 270°C, temperature control of zone 6 at 270°C, head temperature at 265°C, melt temperature at 233°C, main engine current at 13A, main engine speed at 60RPM, and feed speed at 15rpm to obtain modified nylon 66.
[0064] Using the UL94-2018 test standard, the modified nylon 66 achieved V0 flame retardancy, and its limiting oxygen index (LOI) was >27%.
[0065] Application Example 6 Take 2000 g of nylon 66 (INVISTA Nylon Chemical (China) Co., Ltd., PA66 U3600 NC01) and 120 g of the organic-inorganic hybrid phosphorus-nitrogen flame retardant powder prepared in Example 6, mix them, and extrude the resulting mixture into granules through a twin-screw extruder under the following conditions: temperature control of zone 1 at 256°C, temperature control of zone 2 at 260°C, temperature control of zone 3 at 265°C, temperature control of zone 4 at 270°C, temperature control of zone 5 at 270°C, temperature control of zone 6 at 270°C, head temperature at 265°C, melt temperature at 233°C, main engine current at 13A, main engine speed at 60RPM, and feed speed at 15rpm to obtain modified nylon 66.
[0066] Using the UL94-2018 test standard, the modified nylon 66 achieved V0 flame retardancy, and its limiting oxygen index (LOI) was >27%.
[0067] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a reactive organic-inorganic hybrid phosphorus-nitrogen flame retardant, comprising the following steps: Mixing inorganic nanoparticles, an epoxy-containing coupling agent and an organic solvent to perform a first modification to obtain coupling agent-modified nanoparticles; The coupling agent-modified nanoparticles are mixed with a first phosphorus compound and subjected to a second modification to obtain reactive phosphorus-containing modified nanoparticles; A phenolic compound, formaldehyde, a nitrogen-containing monomer and an alkaline catalyst are mixed to carry out a polymerization reaction to obtain an intermediate product; The intermediate product is mixed with a second phosphorus compound to carry out a condensation reaction to obtain a reactive phosphorus-nitrogen flame retardant; the second phosphorus compound contains a bifunctional group or a multifunctional group; Compounding the reactive phosphorus-containing modified nanoparticles with a reactive phosphorus-nitrogen flame retardant to obtain a reactive organic-inorganic hybrid phosphorus-nitrogen flame retardant; The first phosphorus compound includes one or more of hydroxymethylphenylphosphinate, hydroxyethylidene diphosphonic acid, 2-carboxyethylphenylphosphinate, 3-hydroxyphenylphosphonic acid, (3-aminophenyl)phosphonic acid, (2-hydroxyphenyl)phosphonic acid, phosphasalicylic acid, phosphoric acid, phosphorous acid and polyphosphoric acid; The second phosphorus compound includes one or more of hydroxymethylphenylphosphinate, hydroxyethylidene diphosphonic acid, 2-carboxyethylphenylphosphinate, 3-hydroxyphenylphosphonic acid, (3-aminophenyl)phosphonic acid, (2-hydroxyphenyl)phosphonic acid, phosphasalicylic acid, phosphoric acid, phosphorous acid and polyphosphoric acid; The molar ratio of the epoxy-containing coupling agent to the first phosphorus compound is 1:0.3-1; The molar ratio of the phenolic compound to the second phosphorus compound is 10:1-5; The mass ratio of the reactive phosphorus-containing modified nanoparticles to the reactive phosphorus-nitrogen flame retardant is 1:1-5.
2. The preparation method according to claim 1, characterized in that: The inorganic nanoparticles include silicon dioxide, titanium dioxide, copper oxide, zinc oxide, montmorillonite or aluminum oxide; The epoxy-containing coupling agent includes KH-560; The mass ratio of the epoxy-containing coupling agent to the inorganic nanoparticles is 1:5-20.
3. The preparation method according to claim 2, characterized in that: The temperature of the first modification is room temperature, and the time is 3-6 hours; the temperature of the second modification is 60-90° C., and the time is 1-3 hours.
4. The preparation method according to claim 1, characterized in that: The phenolic compound includes one or more of phenol, o-cresol, p-cresol, bisphenol A, hydroquinone, resorcinol, catechol and cardanol; the nitrogen-containing monomer includes melamine or urea; the molar ratio of the phenolic compound to the nitrogen-containing monomer is 10:1-5; the molar ratio of the phenolic compound to formaldehyde is 1:0.6-2.
5. The preparation method according to claim 1 or 4, characterized in that: The alkaline catalyst includes ammonia water, sodium hydroxide or potassium hydroxide; the polymerization reaction temperature is 70-100° C., the reaction time is 2-4 hours, and the pH value is 8.
5.
6. The preparation method according to claim 1, characterized in that: The condensation reaction temperature is 80-100° C. and the reaction time is 1-4 hours.
7. A reactive organic-inorganic hybrid phosphorus-nitrogen flame retardant prepared by the preparation method according to any one of claims 1 to 6, characterized in that: The reactive groups contained include hydroxyl or carboxyl groups.
8. Use of the reactive organic-inorganic hybrid phosphorus-nitrogen flame retardant according to claim 7 in polyamide, characterized in that: The application method comprises: mixing and granulating the reactive organic-inorganic hybrid phosphorus-nitrogen flame retardant with polyamide to obtain a composite; the mass of the reactive organic-inorganic hybrid phosphorus-nitrogen flame retardant is 1-40% of the mass of the polyamide.
Citation Information
Patent Citations
Phosphoro-silicate hybrid-containing composite fire retardant and preparation method thereof
CN101818068A
Fire retardants containing phosphorus, nitrogen, and silicon and used for fabric finish and preparation method thereof
CN103161074A
Phosphaphenanthrene compound 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) grafted and modified sepiolite fibers and preparation method thereof
CN103980736A
Phosphorus-containing polymer modified nano-particles and preparation method thereof
CN104891512A
Reactive phosphorus-nitrogen flame retardant as well as preparation method and application thereof
CN116693788A